THE MOTIVATION OF SOCIAL SCIENCE AND SCIENCE STUDENTS IN LEARNING ENGLISH - Vionatha Lengkong; Henny PS Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2014)
This is a quantitative study which examined the influence of background of the study (Social Science and Science) in students’ motivation to learn English. Social Science was represented by Faculty of Economy while Science was represented by Faculty of Industrial Technology. Data collection was done by using survey technique in which 100 respondents from each background of study filled in the questionnaires which were handed to them. Theory used in this study is Socio-Educational Model by Gardner (2005). The result of this study showed that there is no significant difference between Social Science and Science students in learning English. It can be concluded that in Indonesia, background of the study does not have a significant influence in determining students’ motivation to learn English.